2007
DOI: 10.1172/jci32249
|View full text |Cite
|
Sign up to set email alerts
|

Monosaccharide-induced lipogenesis regulates the human hepatic sex hormone–binding globulin gene

Abstract: The liver produces plasma sex hormone-binding globulin (SHBG), which transports sex steroids and regulates their access to tissues. In overweight children and adults, low plasma SHBG levels are a biomarker of the metabolic syndrome and its associated pathologies. Here, we showed in transgenic mice and HepG2 hepatoblastoma cells that monosaccharides (glucose and fructose) reduce human SHBG production by hepatocytes. This occurred via a downregulation of hepatocyte nuclear factor-4α (HNF-4α) and replacement of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
225
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(244 citation statements)
references
References 39 publications
15
225
4
Order By: Relevance
“…The possibility that expression of the human SHBG gene in the liver responds to an increased exposure to monosaccharides, rather than to insulin has been recently explored. Using transgenic mice expressing human SHBG transgenes and HepG2 human hepatoblastoma cells, Selva et al (2007) reported that glucose and fructose reduce human SHBG production by hepatocytes, via a down-regulation of hepatic HNF-4 levels in concert with parallel increases in cellular palmitate levels. Moreover, inhibition of lipogenesis prevented monosaccharide-induced down-regulation of HNF-4 and reduced the concomitant down-regulation of SHBG expression in HepG2 cells.…”
Section: Effects Of Insulin and Monosaccharidesmentioning
confidence: 99%
“…The possibility that expression of the human SHBG gene in the liver responds to an increased exposure to monosaccharides, rather than to insulin has been recently explored. Using transgenic mice expressing human SHBG transgenes and HepG2 human hepatoblastoma cells, Selva et al (2007) reported that glucose and fructose reduce human SHBG production by hepatocytes, via a down-regulation of hepatic HNF-4 levels in concert with parallel increases in cellular palmitate levels. Moreover, inhibition of lipogenesis prevented monosaccharide-induced down-regulation of HNF-4 and reduced the concomitant down-regulation of SHBG expression in HepG2 cells.…”
Section: Effects Of Insulin and Monosaccharidesmentioning
confidence: 99%
“…For experiments, HepG2 cells were cultured to 30-50% confluence prior to the addition of supplements: glucose (Sigma-Aldrich Canada Ltd), T 3 (Sigma-Aldrich), T 4 (Sigma-Aldrich) or etomoxir (Sigma-Aldrich), as indicated. Palmitate levels in HepG2 cells were determined as described previously (Selva et al 2007).…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
“…Transient transfections of human SHBG promoterdriven luciferase reporter plasmids together with a pCMVlacZ control plasmid , Selva et al 2007 were performed using the HiPerfect Transfection Reagent (Qiagen). The siRNA experiments were carried out using HiPerfect Transfection Reagent together with either a control siRNA (catalog 1022076) or an hepatocyte nuclear factor-4a (HNF-4a) siRNA (catalog 00161546) obtained from Qiagen.…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially the case in patients with low SHBG, which contributes per se to clinical hyperandrogenism. It is well documented that insulin resistance (45), liver lipogenesis and/or inflammation (46,47) decrease SHBG levels by a well-identified mechanism in the liver expression of SHBG gene. In addition, it is also documented that androgen excess reduces the inhibition of gonadotropin-releasing hormone pulse frequency normally exerted by progesterone, causing rapid LH pulse secretion and further maintaining or increasing ovarian androgen production (48).…”
Section: The Free-hormone Hypothesismentioning
confidence: 99%